Single dopaminergic neurons that modulate aggression in Drosophila - Alekseyenko, Olga V. (National Academy of Sciences, 2013)
Monoamines, including dopamine (DA), have been linked to aggression in various species. However, the precise role or roles served by the amine in aggression have been difficult to define because dopaminergic systems influence many behaviors, and all can be altered by changing the function of dopaminergic neurons. In the fruit fly, with the powerful genetic tools available, small subsets of brain cells can be reliably manipulated, offering enormous advantages for exploration of how and where amine neurons fit into the circuits involved with aggression. By combining the GAL4/upstream activating sequence (UAS) binary system with the Flippase (FLP) recombination technique, we were able to restrict the numbers of targeted DA neurons down to a single-cell level. To explore the function of these individual dopaminergic neurons, we inactivated them with the tetanus toxin light chain, a genetically encoded inhibitor of neurotransmitter release, or activated them with dTrpA1, a temperature-sensitive cation channel. We found two sets of dopaminergic neurons that modulate aggression, one from the T1 cluster and another from the PPM3 cluster. Both activation and inactivation of these neurons resulted in an increase in aggression. We demonstrate that the presynaptic terminals of the identified T1 and PPM3 dopaminergic neurons project to different parts of the central complex, overlapping with the receptor fields of DD2R and DopR DA receptor subtypes, respectively. These data suggest that the two types of dopaminergic neurons may influence aggression through interactions in the central complex region of the brain involving two different DA receptor subtypes.